EFL Students’ Difficulties in Answering Listening TOEFL of Short Dialogue Test - Endah Anisa Rahma; Giovanni Oktavinanda; Veni Nella Syahputri; Rusma Setiyana; Ana Elvia Jakfar (Universitas Serambi Mekkah, 2022)
This study investigates the most difficult parts in listening comprehension test faced by undergraduate students from Universitas Teuku Umar. The subject was 30 students who have taken the TOEFL test more than three times. The study used descriptive qualitative research. The data were taken from students’ TOEFL score and interview. This study focused on 13 aspects of short dialogues (synonym, similar sound, Who, What and Where, Passive, Negative Expression, Double Negative, Negative with Comparative, “Almost Negative”, Expression of Surprise, Expression of Agreement, Uncertainty and Suggestion, Wishes and Untrue Condition, Idiomatic Expression) which adopted from Longman Complete Course for the TOEFL Test. The result found that the most difficult aspects in listening comprehension of short dialogue test were similar sound, uncertainty and suggestion, idiom words, and synonym. It was revealed that the most difficult aspect in listening Part A (short dialogue) is similar sound that was proven from students’ incorrect answer (97%), only 3% of them answered correctly, followed by Uncertainty and Suggestion (94%) and idiom words (94%), only 2% of students answered correctly from each of the aspect, and synonym (90%), 3% of them chose the right answers. The result of interview found that most of them got unfamiliar with the sound, lack of practice and low motivation in learning a foreign language. It can be stated that the most difficult aspect in listening short dialogue is similar sound and the factors that cause them hard to answer short dialogue part come from external (unfamiliar sound) and internal problems (lack of practice and low motivation). Keywords: Listening Comprehension, Short Dialogue Problems, TOEFL Test.